Enam Motif Batik Klasik dan Satu Lurik dalam Sistem Nilai Ritual Mitoni Masyarakat Surakarta - BUDI, Setyo (PPS ISI Yogyakarta, 2017)
Originally, batik is a work of art that was created for the clothing ofaristocrats and for use in traditional Javanese rituals. The philosophicalmeaning and value of batik cannot be understood without looking back at theconcepts of space and time when it was first created, namely for traditionalrituals. Mitoni is a traditional ritual which continues to take place today,especially in the Surakarta community, and is consistent in its use of batikmaterial, specifically using six pieces of cloth with classical Surakarta batikmotifs and one piece of lurik as its main materials.The research method used for investigating and explaining batik withinthe system of ritual values with a socio-cultural background is an explorativeexplanativeQualitative Research, supported by an Ethnographic Perspective,a Theory of Iconographic, and a Hermeneutics Approach.The Mitoni ritual is communal celebration which is part of the recurringlife cycle of the Javanese community and is held for a woman in the seventhmonth of pregnancy. The stages that make up the ritual procession include:setting the time and place for the ritual, Tulak-balak, Sêsajèn, Sungkêman,Siraman, Brojolan, Nyampingan, and Jangkêpan. It is a ritual that involvesnumerous symbols based on the number seven, in accordance with theimplementation and purpose of the rite. The synergy between the symbols,mantras, and procession form the value-system construct of the ritual. Thepresence of six pieces of classical Surakarta batik material, with the motifs ofSidoasih, Sidodadi, Sidomukti, Sidodrajat, Sidomulyo, and Sidoluhur with aMandala pattern, and a piece of lurik cloth with the Tumbar Pêcah motif,function as the source of ‘metaphysical energy for the rite’. This energy of themandala is installed into the metaphysical body of the baby inside the womb.The Surakarta community, which memetically lives in a syndrome of povertyand oppression as a result of the Cultuurstelsel of the 19th century, isendeavouring to free its descendants from this trauma through thetranscendence of the ritual. Hence, the seven pieces of material are the mainelement of perfection in the value system of the Mitoni ritual and thisculminates in the “value of conviction”, that the Mitoni ritual is the power offreedom from the past and the power of freedom for the future.Keywords: Batik, Lurik, Mitoni, Ritual, Value-system.